Molecular characterization of severin from Clonorchis sinensis excretory/secretory products and its potential anti-apoptotic role in hepatocarcinoma PLC cells. - Xueqing Chen; Shan Li; Lei He; Xiaoyun Wang; Pei Liang; Wenjun Chen; Meng Bian; Mengyu Ren; Jinsi Lin; Chi Liang; Jin Xu; Zhongdao Wu; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND: Clonorchiasis, caused by the infection of Clonorchis sinensis (C. sinensis), is a kind of neglected tropical disease, but it is highly related to cholangiocarcinoma and hepatocellular carcinoma (HCC). It has been well known that the excretory/secretory products of C. sinensis (CsESPs) play key roles in clonorchiasis associated carcinoma. From genome and transcriptome of C. sinensis, we identified one component of CsESPs, severin (Csseverin), which had three putative gelsolin domains. Its homologues are supposed to play a vital role in apoptosis resistance of tumour cell. METHODOLOGY/PRINCIPAL FINDINGS: There was significant similarity in tertiary structures between human gelsolin and Csseverin by bioinformatics analysis. We identified that Csseverin expressed at life stage of adult worm, metacercaria and egg by the method of quantitative real-time PCR and western blotting. Csseverin distributed in vitellarium and intrauterine eggs of adult worm and tegument of metacercaria by immunofluorence assay. We obtained recombinant Csseverin (rCsseverin) and confirmed that rCsseverin could bind with calciumion in circular dichroism spectrum analysis. It was demonstrated that rCsseverin was of the capability of actin binding by gel overlay assay and immunocytochemistry. Both Annexin V/PI assay and mitochondrial membrane potential assay of human hepatocarcinoma cell line PLC showed apoptosis resistance after incubation with different concentrations of rCsseverin. Morphological analysis, apoptosis-associated changes of mitochondrial membrane potential and Annexin V/PI apoptosis assay showed that co-incubation of PLC cells with rCsseverin in vitro led to an inhibition of apoptosis induced by serum-starved for 24 h. CONCLUSIONS/SIGNIFICANCE: Collectively, the molecular properties of Csseverin, a molecule of CsESPs, were characterized in our study. rCsseverin could cause obvious apoptotic inhibition in human HCC cell line. Csseverin might exacerbate the process of HCC patients combined with C. sinensis infection.